Psychometric Properties of the Educational Study Demands Questionnaire - Olefir, Valerii; Kotenko, Svitlana (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2025)
The aim of the study was to create a psychometrically sound Ukrainian-language questionnaire of educational environment requirements. The development was based on a model of work and learning requirements and resources adapted to the student context: the Scale of Learning Requirements and Resources by K. Mokgele and S. Rothman and the Questionnaire of Work Requirements and Resources by A. Baker. Based on the analysis of existing tools and theoretical provisions, an initial version of the questionnaire was formed, including three scales: academic load, clarity of requirements and adequacy of requirements. The study was conducted on a sample of 283 students of Ukrainian universities (quantitative ratio – 61.0% women, 39.0% men; Mage = 20, SD = 1.5). Statistical analyses were performed using R and RStudio software. The bruceR (Bao, 2023) and lavaan (Rosseel, 2012) packages were used to calculate descriptive statistics, assess reliability, conduct confirmatory factor analysis (CFA) and analyze measurement invariance. Statistical analysis, in particular confirmatory factor analysis, confirmed the three-factor structure of the questionnaire and its high reliability. The measured invariance of the questionnaire by gender was established: both men and women perceive the questionnaire items equally. The results obtained indicate the validity of the developed tool for assessing the requirements of the educational environment, which can be used in psychological research and educational practice.